How Do Parents Respond to Regulation of Sugary Drinks in Child Care? Evidence from California - Jiafei Hu; Rigissa Megalokonomou; Haishan Yuan (Institute of Labor Economics (IZA), 2019)
To reduce sugar intake in children, California regulates the provision of sugar-sweetened beverages and juice by child care facilities. The regulation may reduce children's consumption of sugary beverages in the short run and weaken their preferences for sugary drinks in the long run. Whether these objectives are achieved depends on how parents respond to the regulation by providing sugary drinks at home. Using detailed scanner data of grocery purchases, we find that affected California households increased their juice purchases right after the regulation became effective. However, this increase disappears after one year. Moreover, we find no increase in the purchases of sugary substitutes. Our findings suggest that parents provide more juice for their children after child cares limit their juice provision, but such offsetting behavior disappears after one year. Regulating the consumption of sugary drinks in child cares may be an effective policy to lower children's preferences for sugary drinks.
Keywords: O15; O18; P16; H54; 330; obesity; health; sugary beverage; children; child care regulation